The United States in decline - Lachmann, Richard (Emerald, 2014)
The essays in this volume examine finance, industry and strategy both internally and on a global scale. Contributors clarify our understanding of the current state and future trajectory of the United States and the effect of decline on its citizens and the world.
Includes index.
Keywords: Political Science -- History & Theory.; Political science & theory.; Geopolitics.; Social theory.; United States -- History -- 20th century.; United States -- History -- 21st century.; United States -- Politics and government -- 20th century.; United States -- Politics and government -- 2001-2009.; elektronické knihy; electronic books